*t *and 2 3rds = 4

5 sqrt x+ 1 = 3

2/3 =2 - 5x-3 over x-1

*t *and 2 3rds = 4

5 sqrt x+ 1 = 3

2/3 =2 - 5x-3 over x-1

Tutors, please sign in to answer this question.

I am not sure if I have your equations correct, so please correct me if any of these are set up wrong.

1. t + 2/3= 4 Given

t + 2/3 - 2/3 = 4 - 2/3 Subtract 2/3 from each side

t = 10/3 Simplify

2. 5√(x + 1) = 3 Given

5√(x + 1)/5 = 3/5 Divide each side by 5

√(x + 1) = 3/5 Simplify

x + 1 = (3/5)^{2} Square both sides

x + 1 = 9/25 Simplify

x + 1 - 1 = 9/25 - 1 Subtract 1 from each side

x = - 16/25 Simplify

3. 2/3 = 2 - (5x - 3)/(x - 1) Given

2/3 - 2 = 2 - (5x - 3)/(x - 1) - 2 Subtract 2 from each side

-4/3 = -(5x - 3)/(x - 1) Simplify

-4/3(x - 1) = -(5x - 3) Multiply both sides by x - 1

-4/3x + 4/3 = -5x + 3 Distribute the -4/3 on the left and the - on the right

-4/3x + 4/3 + 5x = 3 Add 5x to each side

11/3x + 4/3 = 3 Simplify

11/3x = 3 - 4/3 Subtract 4/3 from each side

11/3x = 5/3 Simplify

x = 5/3 * (3/11) Multiply both sides by 3/11

x = 5/11 Simplify